Economic Policies for the Sustainability Transition - Roberto Zoboli; Massimiliano Mazzanti; Simone Tagliapietra (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue comprises original research contributions on the changing landscape of sustainability policies and their economic and social impacts. The first paper duscusses the 'green growth' and 'de-growth' recipes for global climate change. The other ten papers address the transition policies of two major actors of the world system: the European Union (five papers) and China (five papers). The papers show that, in spite of the huge differences between the EU27 and China, in both cases, environmental and climate energy policies, as well as circular economy policies, can be effective in driving the sustainability transition or some of its core processes. Effectiveness emerges for a broad range of different policy approaches. A clear-cut conclusion emerging from the papers is that innovation, technological, social or institutional, is the key lever to make policies effective.
Keywords: 330; environmental regulation; Taiwanese investment in mainland China; system GMM; clean energy technologies; European Green Deal; dynamic computable general equilibrium model; policy complexity; revenue recycling; technological spillovers; systems thinking; sustainable energy transition; construction sector; circular economy; policies; recycling; reuse; green total factor productivity; inter-industry factor allocation; EBM-ML model; instrumental variable method; green growth; degrowth; decoupling; Kaya identity; climate change; resource-based cities; environmental information disclosure; high-quality development; PSM-DID method; mediating effects; system generalized method of moments; transmission mechanism; carbon emission; low-carbon pilot city policies; high-quality economic development; industrial structure; urban innovation; regional integration; carbon emission performance; DID model; Yangtze River Economic Belt; waste recycling; quality of institutions; trust in institutions; circular economy action plan; strategic autonomy; green transition; n/a